Armed conflict as a determinant of children malnourishment: a cross-sectional study in The Sudan - Rihab Dahab; Laia Bécares; Mark Brown (BMC, 2020)
Abstract Background Children's nutritional status influences their physical, socioemotional and cognitive development throughout the life course. We aimed to determine the role of armed conflict on the prevalence of childhood malnourishment in The Sudan, and understand the underlying mechanisms using a framework based on the social determinants of health. Methods We analysed cross-sectional data from the 2014-Sudan Multiple Indicator Cluster Survey (n = 14,081) to compare the prevalence of malnourishment in states undergoing armed conflict and states free of conflict. Four-level multilevel multivariate modelling was conducted to identify the contribution of the social determinants of malnourishment in explaining the role of armed conflict in child health, with conflict status as the central predictor and progressive adjustments for child-, household- and cluster- and state-level predictors. Results Armed conflict is strongly associated with greater risk of severe and moderate underweight among children under-5. Adjusting for key social determinants of health reduced the strength of the association between armed conflict and risk of underweight, but there is statistical evidence of association between armed conflict and risk of severe underweight (OR: 1.60, 95%CI: 1.03-2.49 for the low intensity group). Conclusion Conflict-exposed children are particularly vulnerable to malnourishment, and this association is mostly explained by key socio-demographic factors. With the prolonged political instability in The Sudan, sustainable nutritional interventions are necessary to ease hard conditions in conflict-exposed states, and also among disadvantaged families in conflict-free regions.